2018
DOI: 10.1093/jxb/ery041
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic variation in Sorghum bicolor strigolactones and their role in resistance against Striga hermonthica

Abstract: Sorghum is an important food, feed, and industrial crop worldwide. Parasitic weeds of the genus Striga constitute a major constraint to sorghum production, particularly in the drier parts of the world. In this study we analysed the Striga germination stimulants, strigolactones, in the root exudates of 36 sorghum genotypes and assessed Striga germination and infection. Low germination-stimulating activity and low Striga infection correlated with the exudation of low amounts of 5-deoxystrigol and high amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 54 publications
6
25
2
Order By: Relevance
“…The results obtained from SL profiling in sorghum roots and exudates confirmed the differences between the 5-DS producing genotype Shanqui Red and the low S. hermonthica germination stimulant, mostly orobanchol producing SRN39 [50,54]. In Shanqui red, strigol-type SLs represented 99% of the total amount of SLs in the root exudate, with 5-DS being the most abundant and the only one detectable in root tissue (Table 3).…”
Section: Strigolactone Quantitation In Root Tissue and Exudates Of Plsupporting
confidence: 61%
See 2 more Smart Citations
“…The results obtained from SL profiling in sorghum roots and exudates confirmed the differences between the 5-DS producing genotype Shanqui Red and the low S. hermonthica germination stimulant, mostly orobanchol producing SRN39 [50,54]. In Shanqui red, strigol-type SLs represented 99% of the total amount of SLs in the root exudate, with 5-DS being the most abundant and the only one detectable in root tissue (Table 3).…”
Section: Strigolactone Quantitation In Root Tissue and Exudates Of Plsupporting
confidence: 61%
“…Using the organic modifier in the extraction solvent was beneficial for an efficient analyte enrichment from the rhizosphere of sand-grown plants. It also decreased the initial sample volume (20 ml) by more than 25-fold compared to previously published procedures [48][49][50]. Moreover, single-step purification of low volumes of root exudates significantly reduces the sample preparation time to < 30 min or < 3 h including the final evaporation step.…”
Section: Extraction Efficiency and Optimization Of Strigolactone Purimentioning
confidence: 90%
See 1 more Smart Citation
“…Several SL-driven developmental modules have been shown to be highly conserved in the plant kingdom, like shoot lateral branching, root hair elongation, leaf aging and crosstalk with most phytohormones. The recent development of SL-based strategies seems endless, going from approaches targeted to the improvement of good agricultural practices (Pavan et al, 2016; Cochetel et al, 2018; Liu et al, 2018a; Mohemed et al, 2018) to the amelioration of human health through the recently revealed apoptotic function of SL mimics in different kinds of cancers and diseases (Modi et al, 2017, 2018; Hasan et al, 2018).…”
Section: Abcg Subfamily and Strigolactone Transportmentioning
confidence: 99%
“…Strategies focused on the alteration of SL synthesis and/or allocation are promising for the promotion of plant biomass production on nutrient scarce soils. Previous projects based on low SL exuding varieties such as NERICA New Rice for Africa (Cissoko et al, 2011) or S. bicolor (Mohemed et al, 2018) proved to be successful by reducing the germination of parasitic weeds in arable lands of subtropical areas. In farm lands with no parasitic weeds, enhanced SL exudation could on the contrary improve mycorrhization and likely plant nutrient uptake.…”
Section: Sl Importance For Crop Designmentioning
confidence: 99%